Penggunaan Agregat Kasar Batu Gunung Salubue Terhadap Beton Mutu Tinggi - Deo Saldi Tanga; Frans Phengkarsa; Desi Sandy (Paulus Civil Engineering Journal, 2021)
Aims of this study is to determine the characteristics and high quality concrete of coarse aggregate originating from Mount Salubue. The test uses a cylindrical specimen with a height of 30 cm with a diameter of 15 cm and a beam of 60 x 15 x 15 cm, on the mechanical properties of the concrete. The number of specimens is 20 cylindrical specimens and 4 beam specimens. The design of the composition of the constituent materials of concrete uses the SNI 03-2834-2000 method. The results showed that the relationship between compressive strength and split tensile strength is 7.323% to the compressive strength value, and the relationship between compressive strength and flexural strength is 11.104% to the compressive strength value. The characteristics of the coarse aggregate of Mount Salubue meet the SNI standards as a concrete mixture and meets the compressive strength of the plan.